PABRA means partnership: Transforming agriculture in Africa together - Buruchara, Robin Arani; Onyango, P.; Rubyogo, Jean-Claude; Mutari, B.; Zulu, R.; Nkalubo, S.; Chirwa, R.; Fenta, B. (Pan-Africa Bean Research Alliance, 2021)
For two decades, the Pan-Africa Bean Research Alliance (PABRA), a partnership developed and facilitated by the International Center for Tropical Agriculture (CIAT) – a CGIAR Research Center – has fostered a pan-African research and development partnership to strengthen the common bean value chain. Common beans are important food legumes and contribute to the food and nutrition security, income generation and enhances production systems in over 32 countries in sub-Saharan Africa.